1995
DOI: 10.1007/bf00028709
|View full text |Cite
|
Sign up to set email alerts
|

How wide can a wide cross be?

Abstract: Wide crosses in wheat are reviewed in relation to various factors that facilitate wide crossing to show that wide crosses can be as wide as one can make them . Included in this review is a particular reference to wheat-wheatgrass (Agropyron complex) crosses and an update on wide crosses of wheat with various genera of Agropyron complex . Hybrid seed set is too variable to predict whether a wide hybrid, where no seed was obtained in one attempt, will not be possible. High crossability genes seem to facilitate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 117 publications
0
64
0
5
Order By: Relevance
“…Two different genomes share the same cytoplasm in F1 hybrids and allopolyploids, though there can be a tendency for one genome to be lost; for example, in some Hordeum hybrids (Bennett et al, 1976). Very wide hybridisations between cereals and other grasses are possible, but only by ovule pollination and early stage embryo rescue (Sharma, 1995). In the Polygonaceae, F. japonica can cross naturally with both F. baldschuanica and Muehlenbeckia taxa to give viable and germinable progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different genomes share the same cytoplasm in F1 hybrids and allopolyploids, though there can be a tendency for one genome to be lost; for example, in some Hordeum hybrids (Bennett et al, 1976). Very wide hybridisations between cereals and other grasses are possible, but only by ovule pollination and early stage embryo rescue (Sharma, 1995). In the Polygonaceae, F. japonica can cross naturally with both F. baldschuanica and Muehlenbeckia taxa to give viable and germinable progeny.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the question of the disparity in ploidy levels of the parents. In cereals, there is some evidence that successful seed production in crosses between ploidy levels is greater when the higher ploidy is the female, rather than the reciprocal (Sharma, 1995). In the Brassicaceae, Scott et al (1998) found that seed abortion occurred in both directions in crosses between 2 Â and 6 Â Arabidopsis plants, suggesting maternal or paternal excess in the endosperm as the cause.…”
Section: Hybrids Within Fallopia Section Reynoutriamentioning
confidence: 99%
“…Marker Assisted Selection (MAS) will facilitate the development of Near Isogenic Lines (NILs) of cultivars with high crossability. These lines can be utilized to produce new triticales, amphidiploids, and to introduce translocations for the introgression of alien genes for abiotic or biotic stress resistance, improving seed quality and yield from other gene pools (Sharma 1995, Molnar-Lang et al 1996, Lelley 2006.…”
Section: Discussionmentioning
confidence: 99%
“…A decade later, Jiang et al (1994) added 38 additional species, including 17 in Elymus and 6 in Leymus, to the list of hybrids. Sharma (1995) reviewed the production of hybrids between wheat and more than 50 perennial species.…”
Section: Production Of New Hybridsmentioning
confidence: 99%